PERAN EMOSI DALAM PENGAJARAN PENDlDlKANJASMANI DAN OLAHRAGA - Setyo Nugroho (Jurnal Cakrawala Pendidikan, 2004)
This analysis is performed to give a description concerning the role of emotions in teaching ofphysical education and sport. Description early with definition ofemotion expressed with results from the perception ofsome happening and described also as a state of physiological and psychological imbalance. Fear, love; and rage are the three "classical" emotions. Emotional arousal is necessary for peak pertormance, however, it is conceded that too much emotional stimulation tend to interfere with the early stages of motor learning. Emotions are involved in any situation, not only in sports situation. The right kind and the approproate amount ofemotional arousal can truly help a student to reach peaks ofachievement, which would not have been possible without it. Measuring success and failure by the number ofwins and losses parameter representing inadvisable action, because too many frustration and too many failures can be debilitating and disorganizing.The true measure ofsuccess for a student must be his achievement in term of his potentials and the degree ofself-fulfillment achieved through participation.